Beneficial Pleiotropic Antidepressive Effects of Cardiovascular Disease Risk Factor Interventions in the Metabolic Syndrome. Issue 7 (26th March 2018) - Frisbee, Stephanie J.; Singh, Sarah S.; Jackson, Dwayne N.; Lemaster, Kent A.; Milde, Samantha A.; Shoemaker, J. Kevin; Frisbee, Jefferson C.
Abstract : Background: Although the increased prevalence and severity of clinical depression and elevated cardiovascular disease risk represent 2 vexing public health issues, the growing awareness of their combined presentation compounds the challenge. The obese Zucker rat, a model of the metabolic syndrome, spontaneously develops significant depressive symptoms in parallel with the progression of the metabolic syndrome and, thus, represents a compelling model for study. The primary objective was to assess the impact on both cardiovascular outcomes, specifically vascular structure and function, and depressive symptoms in obese Zucker rats after aggressive treatment for cardiovascular disease risk factors with long‐term exercise or targeted pharmacological interventions. Methods and Results: We chronically treated obese Zucker rats with clinically relevant interventions against cardiovascular disease risk factors to determine impacts on vascular outcomes and depressive symptom severity. While most of the interventions (chronic exercise, anti‐hypertensive, the interventions (long‐term exercise, antihypertensive, antidyslipidemia, and antidiabetic) were differentially effective at improving vascular outcomes, only those that also resulted in a significant improvement to oxidant stress, inflammation, arachidonic acid metabolism (prostacyclin versus thromboxane A2 ), and their associated sequelae were effective at also blunting depressive symptom severity. Using multivariable analyses, discrimination between the effectiveness of treatment groups to maintain behavioral outcomes appeared to be dependent on breaking the cycle of inflammation and oxidant stress, with the associated outcomes of improving endothelial metabolism and both cerebral and peripheral vascular structure and function. Conclusions: This initial study provides a compelling framework from which to further interrogate the links between cardiovascular disease risk factors and depressive symptoms and suggests mechanistic links and potentially effective avenues for intervention.